Association of IL-37 levels and genetic variants with systemic lupus erythematosus: a meta-analysis - Young Ho Lee; Gwan Gyu Song (Scientific Reports)
Abstract This study examined the association between circulating interleukin-37 (IL-37) levels and systemic lupus erythematosus (SLE), as well as the relationship between IL-37 gene polymorphisms and susceptibility to SLE. Relevant studies were identified through extensive searches of the Medline, Embase, and Web of Science databases up to December 2024. A meta-analysis was conducted to compare serum/plasma IL-37 levels in SLE patients with those in controls and to evaluate the association between IL-37 gene polymorphisms and SLE risk. Twelve studies comprising 1,229 SLE patients and 745 controls were analyzed. The meta-analysis revealed higher IL-37 levels in SLE patients compared to controls (SMD: 0.570, 95% CI-0.070–1.210, p = 0.0803), though the difference was not statistically significant. Subgroup analysis showed a significant association in Asians (SMD: 0.730, 95% CI: 0.151–1.310, p = 0.010), but not in Arabs (SMD: 0.410, 95% CI: -0.780–1.600, p = 0.500). Analysis of the original data indicated significant results (SMD: 1.026, 95% CI: 0.505–1.547, p < 0.001), while the re-calculated data did not. Studies conducted before 2019 revealed a significant association (SMD: 0.906, 95% CI: 0.438–1.374, p < 0.001), unlike more recent studies. Higher IL-37 levels were observed in patients with lupus nephritis, although these findings were not statistically significant. Genetic analysis of IL-37 rs3811047 polymorphism revealed no significant association in Arabs (OR: 1.432, 95% CI: 0.607–3.373, p = 0.413), whereas a significant association was noted in Asians (OR: 0.649, 95% CI: 0.448–0.941, p = 0.023). The meta-analysis demonstrated significantly elevated IL-37 levels in SLE patients among Asians, along with a significant association between IL-37 polymorphisms and SLE.